Prevalence of Antimicrobial Resistance and Infectious Diseases in a Hospitalised Migrant Population in Paris, France, a Retrospective Study - Sarah Stabler; Olivier Paccoud; Léa Duchesne; Marie-Aude Piot; Marie-Aude Piot; Nadia Valin; Dominique Decré; Dominique Decré; Pierre-Marie Girard; Valérie Lalande; Karine Lacombe; Karine Lacombe; et al. (Frontiers Media S.A., 2022)
Objectives: The aim of this study was to estimate the prevalence of anti-microbial resistance (AMR) carriage and its risk factors in hospitalized migrants. Additionally, the prevalence of infectious diseases was evaluated, as well as symptoms of psychological trauma.Methods: We conducted a retrospective monocentric cross-sectional study including all migrant patients recently arrived and hospitalised over a one-year period.Results: Among 101 patients, seventy-nine percent originated from Sub-Saharan Africa. The overall AMR carriage rate was 20.7% [95% CI: 12.4; 28.9%]. We isolated 5/92 methicillin-resistant Staphylococcus aureus strains (5.4%) and 15/92 extended-spectrum beta-lactamase-producing Enterobacteriaceae (16.4%). AMR carriage was associated with older age, region of origin and length of migration. Rates of HIV, HBV, and HCV infection were 39.6%, 32.7%, and 5%, reflecting sampling bias linked to reasons for hospitalization. Eleven percent had serological evidence of treponemasis and 7.8% had Chlamydia trachomatis infection. Symptoms of depression or post-traumatic stress disorder were observed for more than half the patients.Conclusion: It appears essential to offer a systematic and comprehensive post-arrival screening of AMR carriage, infectious diseases and psychological trauma to subjects who experienced migration.